Impact of Covid-19 Pandemic on Institutional Deliveries and Their Perinatal Outcome: A Hospital Based Study - Kayastha, Nirajana; Sindan, Namrata; Shrestha, Sandeep; Thani, Kamal; Shrestha, Sharmila (Journal of Karnali Academy of Health Sciences, 2020)
Background: Current scenario of novel coronavirus (COVID-19) pandemic pose challenge for effective utilization and accessibility of health services. Various interventions introduced countrywide to contain the disease can have indirect impact on essential health services; one of the core area being maternal and newborn health services. Hence, the present study was conducted to determine trend of institutional deliveries and their outcome before and during COVID-19 pandemic. Methods: This was retrospective observational study carried out in Karnali Academy of Health Sciences (KAHS). Data on socio demographic characteristics, obstetrics and perinatal characteristics of cases who delivered over a period of a year from September 2019 till September 2020 was retrieved from maternal and neonatal records. Results: During study period, among 740 women enrolled in study, 418(56.4%) delivered prior to COVID-19 pandemic and 322(43.6%) during pandemic. Monthly trend of institutional deliveries showed a decline in number of deliveries and women receiving adequate antenatal care visits (ANC) during the pandemic. There was increase in incidence of adverse perinatal outcome during pandemic which consisted preterm births (7.3% before vs 9.6% during pandemic), increased neonatal admissions (9.5% before vs 20% during pandemic) and delivery of low birth weight babies (16.2% before vs 18% during pandemic). Conclusion: There was a decrease in antenatal care visits, institutional deliveries with increase in adverse perinatal outcome in our study. These findings call for adoption of effective policies that could be met within our resources for uninterrupted, easy accessibility and availability of maternal and neonatal health services during current pandemic scenario.